Using persuasive discourse strategies to strengthen arguments in school parliamentary - style debates - Balakrishnan, Ganeish; Paramasivam, Shamala (Shanlax International Journals, 2023)
Purpose - This research investigates the use of persuasive discourse strategies to strengthen arguments in parliamentary-style school debates. The research focuses specifically on the use of the three persuasive discourse strategies (quasilogical, presentational and analogical) proposed by Barbara Johnstone (2012). Methodology - The research design employed is action research that is qualitative in nature utilizing discourse analysis as the method for data analysis. Findings - The victory of the winning team can be attributed to the effective use of these three strategies during the debates. The persuasive strategies consisted of repetition, questions, appeals, using logical reasoning, giving examples and storytelling method. The study shows that persuasive discourse strategies, if effectively used to develop the argument structure, will prove to be an effective method to win debates. Significance - The findings of the study are useful for school debaters and teachers, trainers or coachers of school debating teams.